EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14622107 ZenodoArchiveConcept: 14622106 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1085 2405685:KIEIX7NP
Keywords: _r:AddedByMyEducationEvidence

Designing Digital Notifications to Support Teacher Uptake of Data Dashboards - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the fourth in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the extent to which the provision of notifications to pre-primary teachers to view data dashboards impacts learner device usage and learning outcomes. The A/B/C test found no impact on device usage and negligible impact on learning outcomes. This suggests that accompanying data dashboards with notifications did not influence pedagogical practice in a way which impacted on learning. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; notification system An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117643 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1049 ZenodoArchiveConcept: 13117642
Keywords: _r:AddedByMyEducationEvidence

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15366685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1113 ZenodoArchiveConcept: 15366684
Keywords: _r:AddedByMyEducationEvidence

Optimising Session Duration on Digital Personalised Learning Tools for Early Grade Learners - Sun, Chen; Moustafa, Nariman; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the first in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the optimal number of minutes for pre-primary learners on a classroom-integrated digital personalised learning tool to optimise learning outcomes. The A/B/C test found different levels of session duration impacted on literacy and numeracy outcomes, with the findings for numeracy dependent on grade level. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; session duration An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117631 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1046 ZenodoArchiveConcept: 13117630
Keywords: _r:AddedByMyEducationEvidence

Investigating the Impact of Content Repetition on Digital Personalised Learning Tools for Early Grade Learners - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the third in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the impact of repeating learning content for pre-primary learners on learner device usage and learning outcomes. The A/B test found that content repetition had an impact on literacy and numeracy outcomes for PP2 learners. PP2 learners’ usage of the DPL tool was significantly reduced with content repetition. However, considering the small size of the mixed-methods sample, caution should be taken when interpreting these results. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; repetition An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117639 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1048 ZenodoArchiveConcept: 13117638
Keywords: _r:AddedByMyEducationEvidence

Rapid Evidence Review on Remote Teaching and Learning - Pacitto, Julia; Hayat, Amal; Hinks, Jessica; Emerusenge, Aime Parfait; Ullah, Noor; Rabi, Asma (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to teaching practices and pedagogies for emergency remote learning. The main aim of this review is to provide education decision-makers, funders, and implementers (among others) with a clear understanding of the available global evidence on effective practices in teaching when students are educated remotely during emergencies, and to assess the relevance of this evidence for low- and middle-income contexts. The findings of the RER are organised by the following five themes: (i) instructional design for remote learning in emergency contexts; (ii) student engagement and interactivity in emergency remote teaching; (iii) assessment, feedback, and pedagogical adaptation in remote teaching during emergencies; (iv) well-being, ‘Maslow before Bloom’, and pedagogies of care in emergency remote teaching; (v) teacher training and support in remote teaching during crises. It also identifies critical gaps in the literature on emergency remote teaching and learning, and suggest avenues for future productive research to address these gaps. Keywords: Education in Emergencies, remote learning, pedagogy, teaching methods, EdTech, emergency remote teaching An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14967648 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1098 ZenodoArchiveConcept: 14967647
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Testing Digital Timer Tools to Support Early Grade Lesson Delivery - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the second in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates whether introducing a timer alongside digitised lesson plans impacts upon teachers’ lesson plan usage. The A/B test found that providing a timer did not influence how much time teachers spent on digitised lesson plans. While, on average, teachers in the timer group tended to spend less time on lesson plans for literacy and more for numeracy, this was not statistically significant. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; timer; lesson plan An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117635 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1047 ZenodoArchiveConcept: 13117634
Keywords: _r:AddedByMyEducationEvidence

AI in the Classroom: A rapid evaluation of AI-generated lesson plans in Islamabad’s public schools - Aslam, Nawaz; Qureshi, Ghada; Hassan, Syed Mustafa (EdTech Hub, 2025)
This report presents a rapid evaluation of AI-generated lesson plans currently being used in public schools in rural and urban Islamabad under the National Institute of Excellence in Teacher Education (NIETE). These centrally developed, scripted lesson plans are aligned with the national curriculum and built on the Gradual Release of Responsibility (GRR) model, with additional elements of the 5E and Inquiry-Based Learning (IBL) models in science, and the Concrete-Pictorial-Abstract (CPA) model in maths. Using a mixed-methods approach—including teacher surveys, focus group discussions, key informant interviews, and an expert rubric-based review—the study assesses the lesson plans' quality, relevance, and adaptability. Teachers expressed strong support for the lesson plans, especially in terms of reduced workload and structured delivery, though concerns were raised around flexibility, contextual responsiveness, and teacher agency. While the study does not evaluate student learning outcomes, it provides actionable insights and recommendations for improving the design, support, and implementation of AI-generated instructional tools, particularly as the programme scales to other provinces in Pakistan, such as Balochistan. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15077892 ZenodoArchiveConcept: 15077891 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1104 10.53832/edtechhub.1105 10.53832/edtechhub.1107 10.53832/edtechhub.1108 2405685:FR4GREKJ 2405685:XG7G3FDM
Keywords: _r:AddedByMyEducationEvidence